DEVELOPMENT OF TECHNOLOGIES FOR FUNCTIONAL AND SPECIALIZED ANIMAL-BASED FOOD PRODUCTS (Web of Technology: Multidimensional Research Journal, 2024)
The article considers the development of technologies for the production of functional and specialized food products of animal origin. The historical development of this industry is analyzed, key stages and trends are highlighted. Modern technologies and approaches used in various countries are considered. Attention is paid to the use of biotechnology, micronutrients and innovative processing methods to create products with improved properties. The article summarizes foreign experience and discusses the prospects for introducing such technologies into production.